1969
DOI: 10.1136/jech.23.2.65
|View full text |Cite
|
Sign up to set email alerts
|

Physique and family environment in girls attending a Welsh college.

Abstract: It is a curious fact of the biology of the modem population of Britain that, whereas there is little association between menarcheal age and social class (Douglas, 1964;Nisbet and Illesley, 1963), there remain by contrast clear differences in height and weight between children of different socioeconomic groups. These physique differences persist into adulthood (Clements and Pickett, 1957;Thomson, 1959). This contrast between menarcheal age and body size is the more surprising since both share in the well-establ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

1973
1973
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 9 publications
2
6
0
Order By: Relevance
“…With this speculation, amenable to investi-*> I I; Xgation by body composition studies of families, the J t . It I I physique results in the earlier part of this studŷ .1 r t (Dann and Roberts, 1969) do not conflict, for the t regression coefficients of weight and height on family size are negative, whereas those on position in family are positive. 193b.…”
Section: Intra-county Analysismentioning
confidence: 52%
See 1 more Smart Citation
“…With this speculation, amenable to investi-*> I I; Xgation by body composition studies of families, the J t . It I I physique results in the earlier part of this studŷ .1 r t (Dann and Roberts, 1969) do not conflict, for the t regression coefficients of weight and height on family size are negative, whereas those on position in family are positive. 193b.…”
Section: Intra-county Analysismentioning
confidence: 52%
“…Collection of data finally ceased after the 1970 intake, by which time details were available for 2,457 girls. A preliminary note on the study appeared (Dann and Roberts, 1973), and the full analysis of the total is now reported.…”
mentioning
confidence: 99%
“…In contrast to the variations from analysis to analysis that occurred in menarcheal age, the successive analyses of stature were more consistent. The first analysis of stature after the first 7 years of the Swansea data (Dann and Roberts, 1969) showed a rapid increase in mean stature both overall and within social classes, a t a rate, respectively, of +0.30 and +0.34 cm per year. Stature, but not weight or the ponderal index, was significantly associated with year of birth and social class, but not with family size or birth order.…”
Section: Staturementioning
confidence: 99%
“…Earlier studies on girls studying in the Welsh Collage have revealed that family size tends to diminish height whereas position in family increases height (Dann and Roberts 1969). A multidisciplinary explanation for the findings on family size suggests that family resources become "diluted" as family size increases and the result is the various developmental deficits reported by researchers.…”
Section: Discussionmentioning
confidence: 94%